A calculus problem by Rahil Sehgal

Calculus Level 3

+ + + e x 2 y 2 z 2 d x d y d z \large \displaystyle\int_{-∞}^{+∞} \displaystyle\int_{-∞}^{+∞} \displaystyle\int_{-∞}^{+∞} e^{-x^2 - y^2 - z^2} dx \; dy \; dz

The above multiple integral can be expressed in form of π a b π^{ \frac{a}{b}} where a a and b b are coprime positive integers. Then find a + b a+b .


The answer is 5.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

3 solutions

Kushal Bose
Apr 27, 2017

e t 2 d t = 2 0 e t 2 d t \displaystyle \int_{-\infty}^{\infty} e^{-t^2} dt=\displaystyle 2 \int_{0}^{\infty} e^{-t^2} dt ....(Even function)

Put x 2 = z = > 2 x d x = d z x^2=z => 2xdx=dz .Substituting this into integral 2 0 e z . 1 / 2. z d z = Γ ( 1 / 2 ) = π 2 \int_{0}^{\infty} e^{-z} .1/2.\sqrt{z} dz=\Gamma(1/2)=\sqrt{\pi}

Now come to main integral e x 2 d x × e y 2 d x × e z 2 d x = ( π ) 3 = π 3 / 2 \int_{-\infty}^{\infty} e^{-x^2} dx \times \int_{-\infty}^{\infty} e^{-y^2} dx \times \int_{-\infty}^{\infty} e^{-z^2} dx \\ =(\sqrt{\pi})^3=\pi^{3/2}

Guilherme Niedu
Apr 27, 2017

Using polar coordinates:

{ x = r cos ( θ ) sin ( ϕ ) y = r sin ( θ ) sin ( ϕ ) z = r cos ( ϕ ) \large \displaystyle \begin{cases} x = r \cdot \cos(\theta) \cdot \sin(\phi) \\ y = r \cdot \sin(\theta) \cdot \sin(\phi) \\ z = r\cdot \cos(\phi) \end{cases}

0 < r < , 0 < θ < 2 π , π < ϕ < π \large \displaystyle 0 < r < \infty, 0 < \theta < 2\pi, -\pi < \phi < \pi

J = r 2 sin ( ϕ ) \large \displaystyle |J| = r^2 \cdot \sin(\phi)

The integral becomes:

0 2 π 0 π 0 r 2 sin ( ϕ ) e r 2 d r d ϕ d θ \large \displaystyle \int_0^{2\pi} \int_0^{\pi} \int_0^{\infty} r^2 \sin(\phi) e^{-r^2} dr d\phi d\theta

= 0 2 π d θ 0 π sin ( ϕ ) d ϕ 0 r 2 e r 2 d r \large \displaystyle = \int_0^{2\pi} d\theta \int_0^{\pi} \sin(\phi) d\phi \int_0^{\infty} r^2 e^{-r^2} dr

= 4 π 0 r 2 e r 2 d r \color{#20A900} \boxed {\large \displaystyle = 4 \pi \int_0^{\infty} r^2 e^{-r^2} dr}

Now, let us define:

I ( k ) = 0 e k m 2 d m \large \displaystyle I(k) = \int_0^{\infty} e^{-km^2} dm

I ( k ) = 1 2 e k m 2 d m \large \displaystyle I(k) = \frac12 \int_{-\infty}^{\infty} e^{-km^2} dm

I ( k ) 2 = 1 4 e k ( m 2 + n 2 ) d m d n \large \displaystyle I(k)^2 = \frac14 \int_{-\infty}^{\infty} \int_{-\infty}^{\infty} e^{-k\cdot(m^2+n^2)} dm dn

Using polar coordinates, m = ρ cos ( α ) m = \rho \cos(\alpha) , n = ρ sin ( α ) n = \rho \sin(\alpha) , J = ρ |J| = \rho :

I ( k ) 2 = 1 4 0 2 π 0 ρ e k ρ 2 d ρ d α \large \displaystyle I(k)^2 = \frac14 \int_0^{2 \pi} \int_0^{\infty} \rho e^{-k \rho^2} d\rho d\alpha

I ( k ) 2 = 1 4 0 2 π d α 0 ρ e k ρ 2 d ρ \large \displaystyle I(k)^2 = \frac14 \int_0^{2 \pi} d\alpha \int_0^{\infty} \rho e^{-k \rho^2} d\rho

I ( k ) 2 = 1 4 2 π 1 2 k e k ρ 2 0 \large \displaystyle I(k)^2 = \frac14 2\pi \cdot \frac{1}{2k} e^{-k\rho^2} \Bigg | _{\infty}^0

I ( k ) 2 = π 4 k \large \displaystyle I(k)^2 = \frac{\pi}{4k}

I ( k ) = π 4 k \large \displaystyle I(k) = \sqrt{\frac{\pi}{4k}}

0 e k m 2 d m = 1 2 π k \color{#20A900} \boxed {\large \displaystyle \int_0^{\infty} e^{-km^2} dm = \frac12 \sqrt{\frac{\pi}{k}} }

Differentiating with respect to k k in both sides:

0 m 2 e k m 2 d m = 1 4 π k 3 \large \displaystyle - \int_0^{\infty} m^2 e^{-km^2} dm = - \frac14 \sqrt{\frac{\pi}{k^3}}

0 m 2 e k m 2 d m = 1 4 π k 3 \large \displaystyle \int_0^{\infty} m^2 e^{-km^2} dm = \frac14 \sqrt{\frac{\pi}{k^3}}

Making k = 1 k = 1 :

0 m 2 e m 2 d m = 1 4 π \color{#20A900} \boxed { \large \displaystyle \int_0^{\infty} m^2 e^{-m^2} dm = \frac14 \sqrt{\pi} }

Going back to our original integral:

= 4 π 0 r 2 e r 2 d r \large \displaystyle = 4 \pi \int_0^{\infty} r^2 e^{-r^2} dr

= 4 π 1 4 π \large \displaystyle = 4 \pi \cdot \frac14 \sqrt{\pi}

= π 3 2 \color{#20A900} \boxed { \large \displaystyle = \pi ^{\frac32} }

So:

a = 3 , b = 2 , a + b = 5 \color{#3D99F6} a = 3, b = 2 , \boxed { \large \displaystyle a+b=5}

. .
Feb 27, 2021

+ + + e x 2 y 2 z 2 d x d y d z = π 3 2 = π a b a = 3 , b = 2 a + b = 3 + 2 = 5 \displaystyle \int ^ { + \infty } _ { - \infty } \int ^ { + \infty } _ { - \infty } \int ^ { + \infty } _ { - \infty } e ^ { - x ^ { 2 } - y ^ { 2 } - z ^ { 2 } } dx dy dz = \pi ^ { \frac { 3 } { 2 } } = \pi ^ { \frac { a } { b } } \Rightarrow a = 3, b = 2 \Rightarrow a + b = 3 + 2 = \boxed { 5 }

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...